2020
DOI: 10.1007/s40629-020-00157-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare provision for insect venom allergy patients during the COVID-19 pandemic

Abstract: The population prevalence of insect venom allergy ranges between 3–5%, and it can lead to potentially life-threatening allergic reactions. Patients who have experienced a systemic allergic reaction following an insect sting should be referred to an allergy specialist for diagnosis and treatment. Due to the widespread reduction in outpatient and inpatient care capacities in recent months as a result of the COVID-19 pandemic, the various allergy specialized centers in Germany, Austria, and Switzerland have taken… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…45 Other reports in the UK, Portugal, Germany, Austria, and Switzerland have described a significant reduction in VIT initiation during the COVID-19 pandemic. 28,46,47 Early recommendations advised postponing OIT treatment initiation and up-dosing until normal practice restoration. 14,16 Our findings outline that oral immunotherapy (OIT) treatment initiation and dose escalation were continued in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…45 Other reports in the UK, Portugal, Germany, Austria, and Switzerland have described a significant reduction in VIT initiation during the COVID-19 pandemic. 28,46,47 Early recommendations advised postponing OIT treatment initiation and up-dosing until normal practice restoration. 14,16 Our findings outline that oral immunotherapy (OIT) treatment initiation and dose escalation were continued in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…surveyed allergy departments in Germany, Austria and Switzerland and compared the number of initiations of AIT for hymenoptera‐venom from March‐June 2019 to March‐June 2020. The authors indicated a decline of treatment initiations by 48.5% 26 . The authors attributed this reduction to limited hospital capacity and the hesitation of patients to seek hospital care during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The authors indicated a decline of treatment initiations by 48.5%. 26 The authors attributed this reduction to limited hospital capacity and the hesitation of patients to seek hospital care during the pandemic. The discrepancy between the results of the study by Worm et al.…”
Section: Discussionmentioning
confidence: 99%
“…Analiza ta została przeprowadzona w dużych ośrodkach zajmujących się HVA w Austrii, Niemczech i Szwajcarii. Porównano liczbę pacjentów włączonych do terapii wiosną 2019 i 2020 r. -liczba chorych spadła o 50% [18]. Było to spowodowane głównie znacznym zmniejszeniem dostępności leczenia szpitalnego, a także strachem przed zakażeniem SARS-CoV-2 podczas wizyty w ośrodku medycznym.…”
Section: Skuteczność Leczeniaunclassified
“…W ww. krajach powstały nawet specjalne zalecenia, mające na celu zapewnienie ciągłości opieki nad chorymi z HVA w trakcie pandemii [18]: • zwiększenie dostępności wizyt w formie teleporad i wideoporad • zmiana aranżacji poczekalni i wdrożenie środków higienicznych i socjalnych • wprowadzenie zasad dystansowania • współpraca z lekarzami POZ w zakresie diagnostyki podstawowej HVA (oznaczenie sIgE dla jadów osy i pszczoły) • szybkie testy na COVID-19 przed kursami wstępnymi immunoterapii w ramach hospitalizacji • kontynuacja VIT w trybie ambulatoryjnym, z zachowaniem odstępów kolejnych iniekcji • rozpoczęcie immunoterapii jadem owadów w sezonie aktywności owadów schematami rush i ultra-rush; a jeśli to konieczne -korzystanie z protokołów ambulatoryjnych, zwłaszcza poza sezonem aktywności owadów • wyraźne odniesienie się do sytuacji związanej z COVID-19 w trakcie konsultacji lekarskich Rycina 3. Schemat kwalifikacji pacjentów do odczulania jadem owadów (zmodyfikowano na podstawie [11]).…”
Section: Skuteczność Leczeniaunclassified